Kepuasan Kerja sebagai Variabel Mediasi pada Pengaruh Ketidakjelasan Peran terhadap Kinerja Pegawai - Riska Susanti; Rahmi Fahmy (University of Merdeka Malang, 2020)
The purpose of this research is to analyze the effect of role ambiguity on employee performance mediated by job satisfaction. The population in this research is ASN employees (State Civil Servants) at the Puskesmas located in Padang Panjang City. Samples of this research are 108 people that have taken with a purposive sampling technique. The results of this research show: 1) Role ambiguity has a negative and significant effect on employee performance. 2) Role Ambiguity has a negative and significant effect on job satisfaction felt by employees, and 3) Job satisfaction has a positive and significant effect on employee performance, and 4) Job satisfaction acts as a mediating variable of the unclear role on employee performancehttps://doi.org/10.26905/jmdk.v8i1.4001